ADS-B Performance Monitoring and Potential Electromagnetic Interference - Reza Septiawan; I Made Astawa; Siswahyudi Azhari; Widrianto Sih Pinastiko; Nashrullah Taufik; Arief Rufiyanto; Rizky Rahmatullah (IJNMT (International Journal of New Media Technology), 2020)
The integration of unmanned aircraft systems (UAS) into the air traffic management will be very demanding. Surveillance equipments based on Automatic Dependent Surveillance-Broadcast (ADS-B) contribute a significant role for maintaining separations between both UAS and aircraft in order to maintain the requirements of aviation safety and airspace integrity. Performance analysis of ADS-B equipments related to signal quality and potential Electromagnetic/Radio Frequency Interference is very important to mitigate the failure risk in air traffic management. This paper discuss performance test analysis of ADS-B based surveillance equipments related to the most importance performance parameter namely the continuous reception of messages in terms of message drops and probability of update interval message receptions. Another performance test related to electromagnetic emission of ADS-B based surveillance equipments is conducted in order to mitigate potential RF interferences.